TEACHERS’ READINESS IN INSERTING THE 21ST CENTURY SKILLS FOR TEACHING ENGLISH AT PRIMARY SCHOOLS - Rahmayanti, Putu; Padmadewi, Ni Nyoman; Artini, Luh Putu (International Journal of Language and Literature, 2020)
The development of 21st century affects all sectors including the education field. The importance for preparing students with knowledge and skills affects the learning process in this era. Life skills and balanced assessment are the demands in 21st century era. These demands need to be prepared by the teachers since primary education. Therefore, it is important to analyze primary English teachers’ readiness in inserting 21st century skills in terms of lesson planning, teaching and learning process and assessing students’ learning as the important aspect on learning process. This study used embedded mixed method using qualitative description and supported with descriptive quantitative analysis. The subjects of the research were 11 primary English teachers in Denpasar. A questionnaire was used to measure the readiness of the teachers in inserting the skills in the aspects of learning process. The data obtained were calculated and classified into its level of teachers’ readiness. It was found that the teachers perceived themselves as ready in inserting the 21st century skills. This is indicated by 1) their positive responses toward the knowledge about the 21st century skills, 2) they were confident in perceiving their implementation toward 21st century skills, and 3) they were ready in inserting 21st century skills in terms of lesson planning, teaching and learning process and assessing their students’ learning activities. It is expected that the teachers sustain their readiness in inserting the 21st century skills in teaching English for their students at schools.